Analysis of Literacy and Numeracy Skills of Elementary School Students in Solving Mathematical Problems - Novian Riskiana Dewi; Nur Rafika Rahmah; Nurul Hidayah (Formosa Journal of Multidisciplinary Research, 2022)
This research is entitled "Analysis of Literacy and Numeracy Ability of Elementary School Students in Solving Mathematical Problems". This study aims to describe how to analyze the literacy and numeracy skills of fourth grade elementary school students in solving mathematical problems. The research that the researchers conducted was a qualitative descriptive study, to obtain the validity of the data the researcher used data triangulation from several techniques, including observation, interviews and documentation. The data source is primary data consisting of fourth grade students and fourth grade teachers. As for secondary data, namely documentation data regarding SD Negeri 2 Gisting Atas. Furthermore, the data were analyzed qualitatively through data reduction techniques (data reduction), data presentation (display) and drawing conclusions. Based on data analysis, it was found that students with good ability criteria from the three indicators were able to apply the three indicators correctly and appropriately. Students with sufficient ability criteria from the three indicators are quite capable of applying the three indicators correctly even though there are a few difficulties.